Passenger car market and regional price discriminations for new cars: Case study and empirical analysis for Poland 2004–2021 - Bielig Andreas (International Journal of Management and Economics)
Poland disposes on a large stock of mostly aged private passenger cars. In contrast younger cars still play minor role in individual mobility. The contribution analyzes reasons of lagging modernization by focusing on new cars prices with respect to regional price discrimination. It finds in 2004-2021 substantially increasing new cars prices and regional price discrimination between Poland and Germany. Price differentials were positive, with lower prices in Poland, and increased during time. Producers discriminated by prices increasingly but also limited arbitrage transactions by controlling excess differentials. Optimal regional price discrimination could support car markets developments in Poland by stock age compositions shifts towards younger cars. However, applied discrimination proves in observed market environments not sufficient to achieve a great car market transition in near future.